The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.3389/fnagi.2017.00446
|View full text |Cite
|
Sign up to set email alerts
|

Role of Copper in the Onset of Alzheimer’s Disease Compared to Other Metals

Abstract: Alzheimer’s disease (AD) is a neurodegenerative disorder that is characterized by amyloid plaques in patients’ brain tissue. The plaques are mainly made of β-amyloid peptides and trace elements including Zn2+, Cu2+, and Fe2+. Some studies have shown that AD can be considered a type of metal dyshomeostasis. Among metal ions involved in plaques, numerous studies have focused on copper ions, which seem to be one of the main cationic elements in plaque formation. The involvement of copper in AD is controversial, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
146
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(149 citation statements)
references
References 254 publications
(325 reference statements)
3
146
0
Order By: Relevance
“…Conversely, several studies have reported the higher levels of total copper and non-ceruloplasmin-bound copper in the serum of AD patients compared with controls (Bagheri et al 2018). Squitti et al (2018) reported the higher levels of non-ceruloplasmin-bound copper and the similar levels of ceruloplasmin-bound copper in the serum of 385 AD patients compared with 336 healthy controls.…”
Section: Neurological Disordersmentioning
confidence: 97%
See 2 more Smart Citations
“…Conversely, several studies have reported the higher levels of total copper and non-ceruloplasmin-bound copper in the serum of AD patients compared with controls (Bagheri et al 2018). Squitti et al (2018) reported the higher levels of non-ceruloplasmin-bound copper and the similar levels of ceruloplasmin-bound copper in the serum of 385 AD patients compared with 336 healthy controls.…”
Section: Neurological Disordersmentioning
confidence: 97%
“…At the same time, the disturbed bioavailability of copper resulting in deficiency is another feature of AD (Kaden et al 2011), although the mechanisms and the causal relationships of the reduced copper availability in AD are not well understood (Kessler et al 2006;Schafer et al 2007;Klevay 2010;Bost et al 2016;Bulcke et al 2017;Li et al 2017;Bagheri et al 2018;Kardos et al 2018). AD-associated alterations in metal-ion (primarily copper) homeostasis were found in all regions of AD brain tissue (Xu et al 2017), suggesting a pan-cerebral copper deficiency in AD.…”
Section: Neurological Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Copper levels in cerebrospinal fluid of AD patients are 2.2 fold higher than in controls; moreover, increased levels of ceruloplasmin in the brain and in cerebrospinal fluid have been also observed [54]. On the other hand, other studies reveal a significant reduction of copper in hippocampus and amygdala areas, suggesting that abnormal copper compartmentalization in different tissues and organs may be associated with AD [55]. This discrepancy is, at least in part, due to an increase in the free pool of copper with a corresponding reduction in protein-bound copper [56,57].…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…Alzheimer's disease (AD) is a progressive neurodegenerative disease characterized by development of senile plaques in the brain [77]. High levels of polyvalent cations (copper, iron, and zinc) are observed in the senile plaques in the brains of AD patients [78][79][80].…”
Section: Alzheimer's Disease and Coppermentioning
confidence: 99%